Comparison between idiopathic and VEXAS-relapsing polychondritis: analysis of a French case series of 95 patients. Issue 2 (22nd July 2022) - Khitri, Mohamed-Yacine; Guedon, Alexis F; Georgin-Lavialle, Sophie; Terrier, Benjamin; Saadoun, David; Seguier, Julie; le Besnerais, Maelle; De Moreuil, Claire; Denis, Guillaume; Gerfaud-Valentin, Mathieu; Allain, Jean Sebastien; Maria, Alexandre; et al.
Abstract : Objective: A new adult-onset autoinflammatory syndrome has been described, named VEXAS (Vacuoles, E1 Enzyme, X-linked, Autoinflammatory, Somatic). We aimed to compare the clinical characteristics, the laboratory features and the outcomes between idiopathic-relapsing polychondritis (I-RP) and VEXAS-relapsing polychondritis (VEXAS-RP). Methods: Patients from French retrospective multicentre cohort of RP were separated into two groups: a VEXAS-RP and an I-RP. Results: Compared with patients with I-RP (n=40), patients with VEXAS-RP (n=55) were men (96% vs 30%, p<0.001) and were older at diagnosis (66 vs 44 years, p<0.001). They had a greater prevalence of fever (60% vs 10%, p<0.001), of skin lesions (82% vs 20%, p<0.001), of ocular involvement (57% vs 28%, p=0.01), of pulmonary infiltrates (46% vs 0%, p<0.001), of heart involvement (11% vs 0%, p=0.0336) and with higher median C-reactive protein levels (64 mg/L vs 10 mg/L, p<0.001). Seventy-five per cent of the patients with VEXAS-RP had myelodysplastic syndrome (MDS) versus none in I-RP group. The glucocorticoids use, and the number of steroid sparing agents were similar in both groups, but patients with VEXAS-RP had more frequent refractory disease (remission obtained in 27% vs 90%, p<0001). VEXAS-RP was associated with higher risk of death: six patients (11%) died in the VEXAS-RP group after a median follow-up of 37 months and none in the I-RP group after a median follow-up of 92 months (p<0.05). Conclusion: We report the largest cohort of VEXAS-RP, characterised by high prevalence of male sex, fever, skin lesion, ocular involvement, pulmonary infiltration, heart involvement, older age and MDS association.